A method for co-production of hard carbon and white phosphorus from biomass
Patent Information
- Application Number
- CN202610790080.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-03
- Publication Date
- 2026-10-23
AI Technical Summary
[0003]目前,生物质基硬碳的制备主要采用高温单纯炭化方法,该方法制备的硬碳存在孔隙稀少、结构致密、钠离子嵌入通道匮乏、储钠比容量低、倍率性能差等问题
[0023]本发明的技术原理为耦合氧化还原造孔一体化反应:在高温保护气氛中,生物质原料中的木质素、纤维素和半纤维素发生炭化重构形成无定形的硬碳骨架,同时体系内的磷酸与高温炭基体发生氧化还原反应,磷酸被还原生成可冷凝回收的四聚白磷(P4)气态分子,磷酸还原过程中持续释放氢离子、磷氧活性自由基、水蒸气等小分子气体,这些小分子气体在炭基体内部原位刻蚀、贯通孔隙,自发构建微孔结构,既可以为钠离子嵌入/脱出提供充足的传输通道,缩短了离子迁移距离,又可以缓冲储钠过程中的材料体积膨胀,大幅提升了硬碳材料的比容量与循环稳定性,最终使得硬碳材料的首次充电比容量可以达到362mAh/g,显著优于传统工艺制备的商用生物质基硬碳材料。
Smart Images

Figure CN122957818A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of biomass solid waste resource utilization, fine phosphorus chemical industry, and electrochemical energy storage electrode materials, specifically to an integrated method for the simultaneous co-production of high sodium storage hard carbon and industrial white phosphorus from biomass. Background Technology
[0002] Sodium-ion batteries have advantages such as abundant resources, low cost, and high safety. They have begun to gradually replace lithium-ion batteries in large-scale energy storage, low-speed new energy vehicles, and smart home appliances, becoming one of the core development directions of the electrochemical energy storage industry. Hard carbon has excellent sodium storage stability, extremely low plateau potential, and excellent cycle life, making it the most mainstream anode material for sodium-ion batteries.
[0003] Currently, the preparation of biomass-based hard carbon mainly employs a high-temperature simple carbonization method. However, this method produces hard carbon with problems such as sparse pores, dense structure, lack of sodium ion insertion channels, low sodium storage capacity, and poor rate performance. To improve the sodium storage performance of hard carbon, the industry commonly uses activating etchants such as potassium hydroxide, steam, and carbon dioxide for secondary activation modification. However, this secondary activation process significantly increases production costs and process complexity, and the resulting acid and alkali waste liquids and high-temperature exhaust gases cause environmental pollution. Furthermore, the modified hard carbon has too many defects and reduced cycle stability, making it difficult to achieve both high specific capacity and long cycle life. In the phosphorus chemical industry, white phosphorus is a basic industrial raw material. Traditional white phosphorus preparation relies on high-temperature reduction processes of phosphate rock, which not only has problems such as high equipment requirements, high energy consumption, and severe solid waste / exhaust gas pollution, but also a single preparation process, only capable of producing white phosphorus, resulting in low resource added value. In existing technologies, the preparation of biomass-based hard carbon and the chemical production of white phosphorus are independent process systems, resulting in cumbersome processes, high preparation costs, and significant environmental pollution.
[0004] Therefore, developing a method for co-producing high-specific-capacity biomass hard carbon and high-purity white phosphorus in a single process is of great significance. Summary of the Invention
[0005] The purpose of this invention is to provide a method for co-producing hard carbon and white phosphorus using biomass.
[0006] The technical solution adopted in this invention is: A method for co-producing hard carbon and white phosphorus using biomass includes the following steps: 1) The biomass raw material is crushed into biomass powder, then soaked in phosphoric acid solution, and then the product is separated and dried to obtain acid-treated biomass powder; 2) The acid-treated biomass powder is pre-carbonized in a protective atmosphere and then ball-milled to obtain charcoal powder; 3) Carbon powder is placed in a protective atmosphere for carbonization. The solid produced by carbonization is hard carbon, and the gas produced by carbonization is condensed to obtain white phosphorus.
[0007] Preferably, the biomass raw material in step 1) is at least one of balsa wood, birch, oak, beech, bamboo, pulp, lignin, walnut shell, camellia shell, peanut shell, coconut shell, xylose residue, fruit kernel, corn cob, straw, and cellulose powder.
[0008] Preferably, the biomass powder in step 1) has a particle size of less than 180 μm.
[0009] Preferably, the mass ratio of biomass powder to phosphoric acid solution in step 1) is 1:1 to 50.
[0010] More preferably, the mass ratio of biomass powder to phosphoric acid solution in step 1) is 1:10 to 40.
[0011] Preferably, the concentration of the phosphoric acid solution in step 1) is 0.1 mol / L to 10 mol / L.
[0012] More preferably, the concentration of the phosphoric acid solution in step 1) is 0.5 mol / L to 2 mol / L.
[0013] Preferably, the soaking time in step 1) is 0.1h to 24h.
[0014] More preferably, the soaking time in step 1) is 5h to 12h.
[0015] Preferably, the protective atmosphere in step 2) is one of nitrogen atmosphere, argon atmosphere, or nitrogen-argon mixed atmosphere.
[0016] Preferably, the pre-carbonization in step 2) includes the following process: heating from room temperature to 400℃ to 800℃ at a heating rate of 1℃ / min to 10℃ / min, and holding at that temperature for 0.1h to 24h.
[0017] More preferably, the pre-carbonization in step 2) includes the following process: heating from room temperature to 500℃ to 700℃ at a heating rate of 3℃ / min to 7℃ / min, and holding at that temperature for 2h to 5h.
[0018] Preferably, the particle size of the carbon powder in step 2) is less than 48 μm.
[0019] Preferably, the protective atmosphere in step 3) is one of nitrogen atmosphere, argon atmosphere, or nitrogen-argon mixed atmosphere.
[0020] Preferably, the carbonization in step 3) includes the following process: heating from room temperature to 1000℃ to 1400℃ at a heating rate of 1℃ / min to 20℃ / min, and holding at that temperature for 0.1h to 12h.
[0021] More preferably, the carbonization in step 3) includes the following process: heating from room temperature to 1200℃ to 1400℃ at a heating rate of 3℃ / min to 10℃ / min, and holding at that temperature for 2h to 5h.
[0022] The application of hard carbon prepared by the method described above, which utilizes biomass co-production of hard carbon and white phosphorus, in the preparation of sodium-ion batteries.
[0023] The technical principle of this invention is a coupled oxidation-reduction pore-forming integrated reaction: In a high-temperature protective atmosphere, lignin, cellulose, and hemicellulose in biomass raw materials undergo carbonization and reconstruction to form an amorphous hard carbon skeleton. At the same time, phosphoric acid in the system undergoes an oxidation-reduction reaction with the high-temperature carbon matrix. Phosphoric acid is reduced to generate condensable and recoverable tetrameric white phosphorus (P4) gaseous molecules. During the phosphoric acid reduction process, small molecule gases such as hydrogen ions, phosphorus-oxygen active free radicals, and water vapor are continuously released. These small molecule gases etch and penetrate the pores in situ inside the carbon matrix, spontaneously constructing a microporous structure. This can provide sufficient transport channels for sodium ion insertion / extraction, shortening the ion migration distance, and buffering the material volume expansion during sodium storage. This significantly improves the specific capacity and cycle stability of the hard carbon material, ultimately enabling the first charge specific capacity of the hard carbon material to reach 362 mAh / g, which is significantly better than commercial biomass-based hard carbon materials prepared by traditional processes.
[0024] The beneficial effects of this invention are: this invention can co-produce high specific capacity biomass hard carbon and high purity white phosphorus through a single process, without the need for acid washing, coating and other processes. The hard carbon prepared has uniform pores, low defect degree, low oxygen content, excellent conductivity, large specific capacity and excellent cycle stability. The white phosphorus prepared has high purity and is suitable for large-scale industrial application.
[0025] Specifically: 1) Integrated process, high added value of dual products: The single high-temperature carbonization process simultaneously prepares high-performance sodium-ion battery hard carbon anode material and industrial-grade high-purity white phosphorus, breaking the status quo of process separation between the two types of products, increasing the comprehensive utilization rate of resources to over 90%, and greatly improving the economic benefits of industrialization. 2) Self-created pores require no secondary modification and have excellent performance: The pores are created by in-situ reduction of phosphoric acid and gas etching, eliminating the need for subsequent processes such as acid-base activation and high-temperature gas modification, which simplifies the process and reduces environmental pollution; the first charge specific capacity of the prepared hard carbon can reach 362 mAh / g, which is far superior to that of conventional biomass hard carbon (first charge specific capacity is 280 mAh / g to 320 mAh / g), and the cycle stability is excellent. 3) Low energy consumption and green environmental protection: Renewable agricultural and forestry biomass raw materials are used to replace traditional fossil reducing agents; the reaction temperature is lower than the traditional white phosphorus smelting temperature, reducing energy consumption by 15% to 20%; there is no discharge of acid and alkali waste liquid or waste residue, making it green and pollution-free, which meets the development needs of dual-carbon industry. Attached Figure Description
[0026] Figure 1 This is a SEM image of the hard carbon in Example 1.
[0027] Figure 2 The nitrogen adsorption-desorption isotherms are shown for the hard carbon in Example 1 and Comparative Example 1.
[0028] Figure 3 The image shows the pore size distribution of the hard carbon in Example 1 and Comparative Example 1.
[0029] Figure 4 The first charge-discharge curves of the sodium-ion batteries in Example 1 and Comparative Example 1 are shown. Detailed Implementation
[0030] The present invention will be further explained and described below with reference to specific embodiments.
[0031] Example 1: A method for co-producing hard carbon and white phosphorus using biomass includes the following steps: 1) Bamboo is crushed in a crusher and then passed through an 80-mesh sieve to make bamboo powder. Then it is soaked in a 1 mol / L phosphoric acid solution for 12 hours. The mass ratio of bamboo powder to phosphoric acid solution is 1:5. After filtration, the solid is dried to obtain acid-treated bamboo powder. 2) Place the acid-treated bamboo powder in a nitrogen atmosphere, and then control the heating rate to rise from room temperature to 600℃ at a rate of 5℃ / min. Hold the temperature for 3 hours, let it cool naturally to room temperature, and then ball-mill it and pass it through a 300-mesh sieve to obtain charcoal powder. 3) Place the carbon powder in a nitrogen atmosphere, and then control the heating rate to rise from room temperature to 1300℃ at a rate of 5℃ / min. Hold the temperature for 2 hours. Cool the solid produced by carbonization to obtain hard carbon (denoted as BPHC-1300). The gaseous substances produced by carbonization (including gaseous white phosphorus) are condensed with nitrogen to obtain white phosphorus.
[0032] A sodium-ion battery is prepared as follows: 94 mg of the aforementioned hard carbon, 3 mg of conductive agent Super P, 3 mg of sodium carboxymethyl cellulose (CMC; binder) and 0.45 mL of deionized water were added to a homogenizer and homogenized for 15 min to prepare an electrode slurry (black paste). The electrode slurry was then coated onto an aluminum foil (current collector) and dried to form a negative electrode. A sodium sheet was used as the positive electrode, a 1.0 mol / L NaPF6 solution (solvents being EC, DMC, and EMC, with a volume ratio of EC, DMC, and EMC of 1:1:1) was used as the electrolyte, a glass fiber membrane was used as the separator, and a stainless steel shell was used to assemble a CR2032 coin cell to obtain a sodium-ion battery.
[0033] Performance testing: 1) The scanning electron microscope (SEM) image of the hard carbon (BPHC-1300) in this embodiment is shown below. Figure 1 As shown.
[0034] Depend on Figure 1 It can be seen that the surface of hard carbon is relatively smooth, the particles are irregular in shape, and the overall particle size distribution is relatively uniform.
[0035] 2) The nitrogen adsorption-desorption isotherm curve of hard carbon (BPHC-1300) in this embodiment is as follows: Figure 2 As shown.
[0036] Depend on Figure 2 It can be seen that the specific surface area of hard carbon is 121 m². 2 / g.
[0037] 3) The pore size distribution diagram of the hard carbon (BPHC-1300) in this embodiment is as follows: Figure 3 As shown.
[0038] Depend on Figure 3 It can be seen that the pore size of hard carbon is mainly distributed at around 1.2 nm and 2 nm, indicating that it has a rich microporous structure.
[0039] 4) The charge-discharge performance of the sodium-ion battery in this embodiment was tested under a current density of 20 mA / g. The first charge-discharge curve of the sodium-ion battery is shown below. Figure 4 As shown.
[0040] Depend on Figure 4 It can be seen that the sodium-ion battery has a first charge specific capacity of 360 mAh / g, a first discharge specific capacity of 400 mAh / g, a first coulombic efficiency of up to 90%, and a plateau capacity of up to 260 mAh / g, indicating that the hard carbon in this embodiment has excellent electrochemical performance.
[0041] Note: Initial coulombic efficiency (%) = (initial charge specific capacity / initial discharge specific capacity) × 100%.
[0042] Example 2: A method for co-producing hard carbon and white phosphorus using biomass includes the following steps: 1) Bamboo is crushed in a crusher and then passed through an 80-mesh sieve to make bamboo powder. Then it is soaked in a 1 mol / L phosphoric acid solution for 8 hours. The mass ratio of bamboo powder to phosphoric acid solution is 1:10. After filtration, the solid is dried to obtain acid-treated bamboo powder. 2) Place the acid-treated bamboo powder in a nitrogen atmosphere, and then control the heating rate to rise from room temperature to 500℃ at a rate of 5℃ / min. Hold the temperature for 3 hours, let it cool naturally to room temperature, and then ball-mill it and pass it through a 300-mesh sieve to obtain charcoal powder. 3) Place the carbon powder in a nitrogen atmosphere, and then control the heating rate to rise from room temperature to 1300℃ at a rate of 5℃ / min. Hold the temperature for 2 hours. Cool the solid produced by carbonization to obtain hard carbon. The gaseous substances produced by carbonization (including gaseous white phosphorus) are condensed with nitrogen to obtain white phosphorus.
[0043] A sodium-ion battery is identical to the sodium-ion battery of Example 1, except that it uses the hard carbon described in this embodiment.
[0044] According to the test (test method is the same as in Example 1), the specific surface area of the hard carbon in this example is 118 m². 2 / g.
[0045] According to the test (test method is the same as in Example 1), the sodium-ion battery in this example has a first charge specific capacity of 347 mAh / g and a first discharge specific capacity of 388 mAh / g under the condition of a current density of 20 mA / g. The first coulombic efficiency reaches 89%, and the plateau capacity is as high as 243 mAh / g, indicating that the hard carbon in this example has excellent electrochemical performance.
[0046] Example 3: A method for co-producing hard carbon and white phosphorus using biomass includes the following steps: 1) The balsa wood was crushed in a crusher and then passed through an 80-mesh sieve to make balsa wood powder. The powder was then soaked in a 1 mol / L phosphoric acid solution for 12 hours. The mass ratio of balsa wood powder to phosphoric acid solution was 1:2. The powder was filtered, and the solid was dried to obtain acid-treated balsa wood powder. 2) Place the acid-treated balsa wood powder in a nitrogen atmosphere, and then control the heating rate to rise from room temperature to 600℃ at a rate of 5℃ / min. Hold the temperature for 3 hours, let it cool naturally to room temperature, and then ball mill it and pass it through a 300-mesh sieve to obtain charcoal powder. 3) Place the carbon powder in a nitrogen atmosphere, and then control the heating rate to rise from room temperature to 1300℃ at a rate of 5℃ / min. Hold the temperature for 2 hours. Cool the solid produced by carbonization to obtain hard carbon. The gaseous substances produced by carbonization (including gaseous white phosphorus) are condensed with nitrogen to obtain white phosphorus.
[0047] A sodium-ion battery is identical to the sodium-ion battery of Example 1, except that it uses the hard carbon described in this embodiment.
[0048] According to the test (test method is the same as in Example 1), the specific surface area of the hard carbon in this example is 116 m². 2 / g.
[0049] According to the test (test method is the same as in Example 1), the sodium-ion battery in this example has a first charge specific capacity of 362 mAh / g and a first discharge specific capacity of 404 mAh / g under the condition of a current density of 20 mA / g. The first coulombic efficiency is as high as 90%, and the plateau capacity is as high as 254 mAh / g, which shows that the hard carbon in this example has excellent electrochemical performance.
[0050] Example 4: A method for co-producing hard carbon and white phosphorus using biomass includes the following steps: 1) The balsa wood was crushed in a crusher and then passed through an 80-mesh sieve to make balsa wood powder. The powder was then soaked in a 1 mol / L phosphoric acid solution for 8 hours. The mass ratio of balsa wood powder to phosphoric acid solution was 1:2. The powder was filtered, and the solid was dried to obtain acid-treated balsa wood powder. 2) Place the acid-treated balsa wood powder in a nitrogen atmosphere, and then control the heating rate to rise from room temperature to 500℃ at a rate of 5℃ / min. Hold the temperature for 3 hours, let it cool naturally to room temperature, and then ball mill it and pass it through a 300-mesh sieve to obtain charcoal powder. 3) Place the carbon powder in a nitrogen atmosphere, and then control the heating rate to rise from room temperature to 1400℃ at a rate of 5℃ / min. Hold the temperature for 2 hours. Cool the solid produced by carbonization to obtain hard carbon. The gaseous substances produced by carbonization (including gaseous white phosphorus) are condensed with nitrogen to obtain white phosphorus.
[0051] A sodium-ion battery is identical to the sodium-ion battery of Example 1, except that it uses the hard carbon described in this embodiment.
[0052] According to the test (test method is the same as in Example 1), the specific surface area of the hard carbon in this example is 112 m². 2 / g.
[0053] According to the test (the test method is the same as in Example 1), the sodium-ion battery in this example has a first charge specific capacity of 351 mAh / g and a first discharge specific capacity of 387 mAh / g under the condition of a current density of 20 mA / g. The first coulombic efficiency is as high as 91%, and the plateau capacity is as high as 248 mAh / g, which shows that the hard carbon in this example has excellent electrochemical performance.
[0054] Comparative Example 1: A method for preparing hard carbon using biomass, comprising the following steps: 1) Place the bamboo in a crusher to grind it, then pass it through an 80-mesh sieve to obtain bamboo powder; 2) Place the bamboo powder in a nitrogen atmosphere, and then control the heating rate to rise from room temperature to 600℃ at a rate of 5℃ / min. Hold the temperature for 3 hours, then ball mill the powder and pass it through a 300-mesh sieve to obtain charcoal powder. 3) Place the carbon powder in a nitrogen atmosphere, and then control the heating rate to rise from room temperature to 1300℃ at a rate of 5℃ / min. Hold the temperature for 2 hours and let it cool naturally to room temperature to obtain hard carbon (denoted as BHC-1300).
[0055] A sodium-ion battery is identical to the sodium-ion battery of Example 1, except that it uses the hard carbon found in this comparative example.
[0056] Performance testing: 1) The nitrogen adsorption-desorption isotherm curve of hard carbon (BHC-1300) in this comparative example is as follows: Figure 2 As shown.
[0057] Depend on Figure 2 It can be determined that the specific surface area of hard carbon is 20 m². 2 / g.
[0058] 2) The pore size distribution diagram of the hard carbon (BHC-1300) in this comparative example is shown below. Figure 3 As shown.
[0059] Depend on Figure 3 It can be seen that hard carbon has very few microporous structures.
[0060] 3) The charge-discharge performance of the sodium-ion battery in this comparative example was tested under a current density of 20 mA / g. The initial charge-discharge curve of the sodium-ion battery is shown below. Figure 4 As shown.
[0061] Depend on Figure 4 It can be seen that the sodium-ion battery has a first charge specific capacity of 250 mAh / g, a first discharge specific capacity of 307 mAh / g, a first coulombic efficiency of 81%, and a plateau capacity of only 155 mAh / g, indicating that the hard carbon in this comparative example has poor electrochemical performance.
[0062] Comparative Example 2: A method for preparing hard carbon using biomass, comprising the following steps: 1) Bamboo is crushed in a crusher and then passed through an 80-mesh sieve to make bamboo powder. Then it is soaked in a 1 mol / L hydrochloric acid solution for 12 hours. The mass ratio of bamboo powder to hydrochloric acid solution is 1:5. After filtration, the solid is dried to obtain acid-treated bamboo powder. 2) Place the acid-treated bamboo powder in a nitrogen atmosphere, and then control the heating rate to rise from room temperature to 600℃ at a rate of 5℃ / min, keep it at that temperature for 3 hours, and then ball mill it and pass it through a 300-mesh sieve to obtain charcoal powder. 3) Place the carbon powder in a nitrogen atmosphere, and then control the heating rate to rise from room temperature to 1300℃ at a rate of 5℃ / min. Hold the temperature for 2 hours and then let it cool naturally to room temperature to obtain hard carbon.
[0063] A sodium-ion battery is identical to the sodium-ion battery of Example 1, except that it uses the hard carbon found in this comparative example.
[0064] According to the test (test method is the same as in Example 1), the specific surface area of the hard carbon in this comparative example is 34 m². 2 / g.
[0065] According to the test (test method is the same as in Example 1), the sodium-ion battery in this comparative example has an initial charge specific capacity of 258 mAh / g, an initial discharge specific capacity of 323 mAh / g, an initial coulombic efficiency of 80%, and a plateau capacity of only 160 mAh / g, indicating that the hard carbon in this comparative example has poor electrochemical performance.
[0066] Comparative Example 3: A method for preparing hard carbon using biomass, comprising the following steps: 1) Bamboo is crushed in a crusher and then passed through an 80-mesh sieve to make bamboo powder. Then it is soaked in a 1 mol / L phosphoric acid solution for 8 hours. The mass ratio of bamboo powder to phosphoric acid solution is 1:5. After filtration, the solid is washed with water until the washing liquid is neutral. Then it is dried to obtain acid-treated bamboo powder. 2) Place the acid-treated bamboo powder in a nitrogen atmosphere, and then control the heating rate to rise from room temperature to 600℃ at a rate of 5℃ / min, keep it at that temperature for 3 hours, and then ball mill it and pass it through a 300-mesh sieve to obtain charcoal powder. 3) Place the carbon powder in a nitrogen atmosphere, and then control the heating rate to rise from room temperature to 1300℃ at a rate of 5℃ / min. Hold the temperature for 2 hours and then let it cool naturally to room temperature to obtain hard carbon.
[0067] A sodium-ion battery is identical to the sodium-ion battery of Example 1, except that it uses the hard carbon found in this comparative example.
[0068] According to the test (test method is the same as in Example 1), the specific surface area of the hard carbon in this comparative example is 25 m². 2 / g.
[0069] According to the test (test method is the same as in Example 1), the sodium-ion battery in this comparative example has an initial charge specific capacity of 253 mAh / g, an initial discharge specific capacity of 312 mAh / g, an initial coulombic efficiency of 81%, and a plateau capacity of only 157 mAh / g, indicating that the hard carbon in this comparative example has poor electrochemical performance.
[0070] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A method for co-producing hard carbon and white phosphorus using biomass, characterized in that, Includes the following steps: 1) The biomass raw material is crushed into biomass powder, then soaked in phosphoric acid solution, and then the product is separated and dried to obtain acid-treated biomass powder; 2) The acid-treated biomass powder is pre-carbonized in a protective atmosphere and then ball-milled to obtain charcoal powder; 3) Carbon powder is placed in a protective atmosphere for carbonization. The solid produced by carbonization is hard carbon, and the gas produced by carbonization is condensed to obtain white phosphorus.
2. The method for co-producing hard carbon and white phosphorus using biomass according to claim 1, characterized in that: Step 1) The biomass raw material is at least one of the following: balsa wood, birch wood, oak wood, beech wood, bamboo, pulp, lignin, walnut shell, camellia shell, peanut shell, coconut shell, xylose residue, fruit kernel, corn cob, straw, and cellulose powder.
3. The method for co-producing hard carbon and white phosphorus using biomass according to claim 1 or 2, characterized in that: Step 1) The biomass powder has a particle size of less than 180 μm.
4. The method for co-producing hard carbon and white phosphorus using biomass according to claim 1 or 2, characterized in that: The mass ratio of biomass powder to phosphoric acid solution in step 1) is 1:1 to 50; and / or the concentration of phosphoric acid solution in step 1) is 0.1 mol / L to 10 mol / L.
5. The method for co-producing hard carbon and white phosphorus using biomass according to claim 1 or 2, characterized in that: The soaking time in step 1) is 0.1h to 24h.
6. The method for co-producing hard carbon and white phosphorus using biomass according to claim 1, characterized in that: Step 2) The protective atmosphere is one of nitrogen atmosphere, argon atmosphere, or nitrogen-argon mixed atmosphere.
7. The method for co-producing hard carbon and white phosphorus using biomass according to claim 1 or 6, characterized in that: Step 2) The pre-carbonization includes the following process: heating from room temperature to 400℃ to 800℃ at a heating rate of 1℃ / min to 10℃ / min, and holding at that temperature for 0.1h to 24h.
8. The method for co-producing hard carbon and white phosphorus using biomass according to claim 1, characterized in that: Step 3) The protective atmosphere is one of nitrogen atmosphere, argon atmosphere, or nitrogen-argon mixed atmosphere.
9. The method for co-producing hard carbon and white phosphorus using biomass according to claim 1 or 8, characterized in that: Step 3) The carbonization process includes the following steps: heating from room temperature to 1000℃ to 1400℃ at a heating rate of 1℃ / min to 20℃ / min, and holding at that temperature for 0.1h to 12h.
10. The application of hard carbon prepared by the method of biomass co-production of hard carbon and white phosphorus as described in any one of claims 1 to 9 in the preparation of sodium-ion batteries.